Enhancing Tax Compliance Intentions: Analyzing the Influence of Awareness, Attention, and Persuasion Among Future Taxpayers - Della Fadhilatunisa; Andi Naila Quin Azisah Alisyahbana (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This study explores the factors influencing tax compliance intentions among future taxpayers, specifically examining the roles of taxpayer awareness, attention, and persuasion. Employing a quantitative research approach with a cross-sectional design, the study analyzed data from a sample of 278 individuals using the PLS-SEM model, evaluating both measurement and structural models. The results demonstrate that taxpayer persuasion has a significant direct impact on tax compliance, indicating that persuasive communication strategies are highly effective. Additionally, taxpayer awareness directly influences tax compliance and mediates the effects of other variables, highlighting the importance of knowledge and awareness in fostering a compliance mindset. Taxpayer intention serves as a crucial intermediary, translating awareness into compliance behavior. The findings suggest that a multifaceted approach combining awareness campaigns, targeted educational programs, and persuasive communication can significantly enhance compliance rates. These insights are essential for developing effective tax education and communication strategies, ultimately contributing to a more robust and compliant tax system. Future research should further investigate these relationships across diverse demographics to bolster tax compliance efforts comprehensively.